A flexible, ultra-sensitive strain sensor based on carbon nanocoil network fabricated by an electrophoretic method. Issue 28 (5th July 2017) - Li, Chengwei; Pan, Lujun; Deng, Chenghao; Wang, Peng; Huang, Yingying; Nasir, Habib
Abstract : An ultra-sensitive strain sensor has been fabricated and studied, whose sensing medium is a network structure composed of plenty of carbon nanocoils (CNCs) and deposited between two gold electrodes via electrophoresis. Abstract : An ultra-sensitive strain sensor has been fabricated and studied, whose sensing medium is a network structure composed of plenty of carbon nanocoils (CNCs) and deposited between two gold electrodes via electrophoresis. The sensor owns a gauge factor close to 10 000 for tensile strain. A high stability and reproducibility of more than 5000 cycles and a fast response time of approximately 50 ms have been achieved. It has a high sensitivity for bending strain as well. Practically, it has shown an excellent performance in the detection of breathing, wrist pulse, and vibration. The sensor can be fabricated with a facile technology and low cost, suggesting great potential applications in micro-nano electromechanical systems, wearable devices and electronic skins.